Food- and waterborne outbreaks in Spain, 2018-2022 (Boletín Epidemiológico Semanal, 2024)
Introduction: Food- and waterborne diseases have a high potential to cause outbreaks and affect large numbers of people in a variety of settings, leading to public health problems.Method: The Spanish Surveillance Network (RENAVE) Outbreak Database was analysed for the period 2018-2022, from which foodborne outbreaks were selected. Results: In 2022, 612 outbreaks were reported, more than in 2021 (313) and similar to 2018 and 2019. The aetiological agent was identified by the laboratory in 41.72% of the outbreaks, with Salmonella spp. being the most frequent, followed by norovirus and Campylobacter spp. The highest lethality was observed in outbreaks due to mushroom toxins (2.38%) and those due to Listeria monocytogenes (0.18%). The period of the year with the highest number of notified outbreaks was the summer months and egg products were the most frequently implicated food, both at household and collective restoration level. Discussion: In 2022, the number of notified outbreaks was almost double that of 2021, returning to the pre-pandemic of COVID-19 levels, similar to was observed at the European level. As in Europe, the aetiological agent responsible for the highest number of outbreaks was Salmonella spp, mainly associated with egg products. Prevention and control measures for these outbreaks must be targeted to both consumers and food business operators. The importance of completeness of information for reported outbreaks must be emphasized.
Keywords: Foodborne outbreaks; Waterborne outbreak; Salmonellosis; Spain; Epidemiological analysis; RENAVE